Eco-Entrepreneurship Incubation for High Schoolers: Utilizing AI-Driven Vision Recognition in Wetland Conservation - Monry Fraick Nicky Gillian Ratumbuysang; Dwi Atmono; Ananda Setiawan; Syaripudin Bahar; Sharfina Amima; Muhammad Zainadi; Hafid Febriansyah (Communautaire: Journal of Community Service, 2026)
This community service program aims to improve Artificial Intelligence (AI) literacy and strengthen entrepreneurial awareness among students of SMAN 4 Banjarmasin through a digital-based waste sorting learning model in wetland ecosystems. The method applied in this activity is Participatory Technology Development (PTD), which integrates socialization sessions, AI literacy workshops, and hands-on implementation using a web-based application system powered by Gemini AI Vision Recognition. This system is designed to identify wetland waste characteristics that are typically wet, mixed, and contaminated with sediment, making conventional sorting methods less effective. The results of the program show a significant improvement in students’ cognitive understanding, indicated by an increase in the average score from 5.67 in the pre-test to 7.76 in the post-test. In addition, 93.1% of participants reported that they had never interacted with AI technology before, while 91.0% expressed high satisfaction with the learning experience. The implication of this activity is the development of an innovative circular economy-based environmental education model that integrates AI technology into waste management learning. This model is expected to be scalable and adaptable for other schools in wetland regions, enabling the transformation of environmental challenges into opportunities for digital innovation and student entrepreneurship development.